A Simulation Environment for Bio-inspired Heterogeneous Chained Modular Robots. (12th February 2014) - Brunete, Alberto; Hernando, Miguel; Gambao, Ernesto
This paper presents a new simulation environment aimed at heterogeneous chained modular robots. This simulator allows for the testing of the feasibility of the design, the checking of how the modules will perform in the field, and the verifying of the hardware, electronics and communication designs before the prototype is built, saving time and resources. The paper shows how the simulator is built and how it can be set up to adapt to new designs. It also gives some examples of its use showing different heterogeneous modular robots running in different environments.